Peak expiratory flow rate among smokers and non-smokers working in Kathmandu Medical College - Gurung, Preetu (Journal of Chitwan Medical College, 2020)
Background: Cigarette smoking has remained a popular habit since ages. Most people are well aware of the deleterious effects of cigarette smoking yet continue to give a blind eye which deteriorates overall public health. The purpose of the present study was to assess Peak Expiratory Flow Rate among smoking and nonsmoking staffs who work in Kathmandu Medical College. Methods: In this comparative cross-sectional study Peak Expiratory Flow Rate was obtained using Mini Wright’s Peak Flow Meter of 108 smokers and 108 nonsmokers in the age group ranging from 25-45 years. Those who never smoked or who have quit smoking for the past 2 years were grouped as nonsmokers and the smokers with history of smoking at least five or more cigarettes per day for at least two years were included in the study for measuring their Peak Expiratory Flow Rate. Data was collected, compiled and analyzed by using Statistical Package of Social Science (SPSS) software version16. Student ‘t’ test was used for group comparison. Results: The Peak Expiratory Flow Rate value was significantly reduced in the smokers (p value< 0.05). Mean Peak Expiratory Flow Rate was reduced with increasing age of the smokers. However, no significant difference was observed in Peak Expiratory Flow Rate with increase in the number of cigarettes smoked (p value> 0.05). Conclusions: In the study Peak Expiratory Flow Rate among smokers (367.13 ± 74.182) was lower than nonsmokers (471.39±60.842), which was statistically significant proving that cigarette smoking reduced peak expiratory flow rate.